Use of Bacteriophage Amended with CRISPR-Cas Systems to Combat Antimicrobial Resistance in the Bacterial Foodborne Pathogen Listeria monocytogenes - Cameron Parsons; Phillip Brown; Sophia Kathariou (MDPI AG, 2021)
Listeria monocytogenes is a bacterial foodborne pathogen and the causative agent of the disease listeriosis, which though uncommon can result in severe symptoms such as meningitis, septicemia, stillbirths, and abortions and has a high case fatality rate. This pathogen can infect humans and other animals, resulting in massive health and economic impacts in the United States and globally. Listeriosis is treated with antimicrobials, typically a combination of a beta-lactam and an aminoglycoside, and L. monocytogenes has remained largely susceptible to the drugs of choice. However, there are several reports of antimicrobial resistance (AMR) in both L. monocytogenes and other Listeria species. Given the dire health outcomes associated with listeriosis, the prospect of antimicrobial-resistant L. monocytogenes is highly problematic for human and animal health. Developing effective tools for the control and elimination of L. monocytogenes, including strains with antimicrobial resistance, is of the utmost importance to prevent further dissemination of AMR in this pathogen. One tool that has shown great promise in combating antibiotic-resistant pathogens is the use of bacteriophages (phages), which are natural bacterial predators and horizontal gene transfer agents. Although native phages can be effective at killing antibiotic-resistant pathogens, limited host ranges and evolved resistance to phages can compromise their use in the efforts to mitigate the global AMR challenge. However, recent advances can allow the use of CRISPR-Cas (clustered regularly interspaced short palindromic repeats-CRISPR-associated proteins) to selectively target pathogens and their AMR determinants. Employment of CRISPR-Cas systems for phage amendment can overcome previous limitations in using phages as biocontrol and allow for the effective control of L. monocytogenes and its AMR determinants.